Digital Leadership as a Driver of Village Transformation: An Empirical Study in Pleret Village, Bantul Regency - Ramdani, Endah Mustika; Artisa, Rike Anggun; Abubakar, Rodlial Ramdhan Tackbir; Andikaputra, Fikri Aditya Tri (Jurnal Manajemen Pelayanan Publik, 2026)
Digital transformation at the village level aims to improve public service efficiency, expand information access, and promote local economic growth through technology. Its success, however, largely depends on visionary and adaptive leadership. Leaders who possess technological understanding and can inspire their communities play a crucial role in fostering inclusivity and addressing challenges such as limited infrastructure and low digital literacy. This study explores leadership competencies that contribute to successful digital transformation, focusing on Pleret Village as a case study. Using qualitative methods and drawing from both primary and secondary data, the research found that effective digital leadership is supported by leaders’ digital knowledge and skills, as well as managerial competencies. Beyond technological proficiency, strategic planning, regulatory strengthening, and innovation development also proved essential. The findings highlight that Pleret Village represents a best practice model for village-level digital transformation, successfully integrating technology, innovation, and managerial capacity while preserving local wisdom.